2001
DOI: 10.1093/gerona/56.1.b3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Equations for Predicting Stature From Knee Height, and Assessment of Statural Loss in an Older Italian Population

Abstract: We determined the applicability of deriving the stature from knee height in an older Italian population, and, in the same population, we assessed longitudinally the change in stature over a 6-year interval. The standing stature and knee height in a supine position were measured in the entire home-dwelling older (65 + years) population of a small Italian town (N = 606). Stature measured in 1989 and in 1995 was used to assess longitudinal changes in 258 subjects of the same population. Stature derived from knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 10 publications
0
16
0
6
Order By: Relevance
“…Leg length was measured at follow-up rather than baseline but is unlikely to have changed substantially over the intervening period. Limb length has been widely evaluated as a better potential marker of earlier stature than total height since it is less susceptible to change associated with osteoporosis (Zhang et al, 1998;Pini et al, 2001).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leg length was measured at follow-up rather than baseline but is unlikely to have changed substantially over the intervening period. Limb length has been widely evaluated as a better potential marker of earlier stature than total height since it is less susceptible to change associated with osteoporosis (Zhang et al, 1998;Pini et al, 2001).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…People with a low level of education are likely to share a variety of other stressors in their early life time, such as poor nutrition, infection, and reduced access to medical care, which have important effects on growth and development. Leg length is an important potential proxy for early life environment since it has been found to be particularly influenced by childhood nutritional status (Wadsworth et al, 2002) and is a component of adult height relatively preserved into late life, as distinct from trunk length (and therefore total height) which is markedly affected by osteoporosis and vertebral collapse (Bannerman et al, 1997;Zhang et al, 1998;Pini et al, 2001). A community study in an older Korean population found an independent association between shorter limb length and dementia and AD (Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In general, elderly males have larger standing dimensions compared to elderly females, i.e. stature, standing knee height and span (Bermúdez et al, 1999;Payette et al, 2000;Pini et al, 2001;Mendoza-Núñez et al, 2002;Palloni et al, 2005;Shahar and Pooy, 2003). Indeed, the studies cited here have shown that elderly males have larger stature and standing knee height by 5e10% compared to elderly females, which is similar to the results obtained in this study.…”
Section: Comparison Of Anthropometric Dimensions With Elderly Populatmentioning
confidence: 99%
“…This works because the limbs used in this literature do not generally shrink as people age. Lower leg length (Chumlea, Roche, and Steinbaugh 1985; Chumlea and Guo 1992; Protho and Rosenbloom 1993; Myers, Takiguchi, and Yu 1994; Zhang, Hsu-Hage, and Wahlqvisl 1998; Bermúdez, Becker, and Tucker 1999; Li et al 2000; Cheng, See, and Shieh 2001; Pini et al 2001; Knous and Arisawa 2002), arm span from roughly the shoulder to the wrist (Kwok and Whitelaw 1991; Kwok, Lau, and Woo 2002), total arm length (Mitchell and Lipschitz 1982; Haboubi, Hudson, and Pathy 1990; Auyeung and Lee 2001), upper arm or humeral length, tibia length (Haboubi, Hudson, and Pathy 1990) and fibula length (Auyeung and Lee 2001) have all been employed to estimate pre-shrinkage stature.…”
mentioning
confidence: 99%